2004
DOI: 10.1023/b:abme.0000017541.82498.37
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the in Vivo Pathomechanics of Osteoarthritis at the Knee

Abstract: The in vivo pathomechanics of osteoarthritis (OA) at the knee is described in a framework that is based on an analysis of studies describing assays of biomarkers, cartilage morphology, and human function (gait analysis). The framework is divided into an Initiation Phase and a Progression Phase. The Initiation Phase is associated with kinematic changes that shift load bearing to infrequently loaded regions of the cartilage that cannot accommodate the loads. The Progression Phase is defined following cartilage b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
779
2
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 885 publications
(838 citation statements)
references
References 88 publications
28
779
2
8
Order By: Relevance
“…The motion of the knee was determined by relating the motion of the marker clusters to the anatomical coordinate systems. Details of the axes orientations of the femoral and tibial anatomic coordinate systems have been described previously (Andracchi 2003, 2005, Dyrby and Andriacchi 2004, Scanlan et al, 2010. The pelvic and foot coordinate systems and corresponding hip and ankle joint complex coordinate systems followed the ISB recommendations (Wu et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The motion of the knee was determined by relating the motion of the marker clusters to the anatomical coordinate systems. Details of the axes orientations of the femoral and tibial anatomic coordinate systems have been described previously (Andracchi 2003, 2005, Dyrby and Andriacchi 2004, Scanlan et al, 2010. The pelvic and foot coordinate systems and corresponding hip and ankle joint complex coordinate systems followed the ISB recommendations (Wu et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…One important marker and target for non-invasive intervention is the first peak of the external knee adduction moment in walking (Miyazaki et al, 2002). It is a surrogate marker of the relative load on the medial compartment (Schipplein and Andriacchi, 1991) and has been correlated with OA radiographic severity, rate of disease progression and severity of disease symptoms (Andriacchi et al, 2004;Andriacchi et al, 2009;Andriacchi and Mundermann, 2006;Astephen et al, 2007;Baliunas et al, 2002;Sharma et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A s noted above, it has been suggested that knee cartilage adapts to the cyclic loading that is specific to walking 1,3 . An examination of the regional variation of healthy cartilage thickness indicates that the thickest cartilage is in the loadbearing areas of the tibiofemoral articulation, which are in contact during the stance phase of walking, when the knee is near full extension.…”
Section: Cartilage Morphology and Walking Mechanicsmentioning
confidence: 97%
“…The importance of walking in the context of cartilage homeostasis suggests that the knee cartilage becomes conditioned 2 to both the load and the number of load cycles associated with walking. Thus, an activity like walking, the most common activity of daily living as well as one that produces a large cyclically reproducible pattern of loading, should be an important consideration in the analysis of the maintenance of the structure, organization, and biology of healthy knee cartilage 3 . Likewise, the mechanics of walking can influence the initial breakdown of cartilage 4 if the normal patterns of loading are changed due to injury or other conditions that would alter the normal balance between loading and the biological maintenance of healthy cartilage [5][6][7] .…”
mentioning
confidence: 99%
“…According to Whiting and Zernicke 2 , prolonged physical exercise in animals can produce hypertrophy of the chondrocytes and an increase in their number. The articular kinematics may promote the reduction or increase in the number of chondrocytes 38 , with a consequent alteration in the composition and organization of the cartilage matrix 39 . Thus, both the decrease in weight bearing caused by the nervous injury and the increase generated by the exercise, mechanically change the cartilage, resulting in changes in the density of chondrocytes.…”
Section: Discussionmentioning
confidence: 99%